Neighbor Discovery in Distributed Heterogeneous Wireless Networks using Cognitive Radio - Khawse, Pravin; S.P. Chhaware (International Journal of Computer Sciences and Engineering, 2014)
In many wireless networks, each node has direct radio link to only a small number of other nodes, called its neighbors. Before efficient routing or other network-level activities are possible, nodes have to discover and identify their neighbors. This is called neighbor discovery. By neighbor discovery, every node tries to determine the set of nodes it can communicate within one wireless hop Fast and efficient discovery of all neighboring nodes by a node new to a neighborhood is Essential and critical to the deployment of wireless networks. The recently emerged technology Cognitive radio (CR) has a promising approach to improve the available spectrum utilization efficiency so as to meet the increased demand for wireless communication, which attempts to search for unused or underutilized channels in the spectrum by scanning the part of wireless spectrum.